Sensitivity analysis of Dengue transmission: Impact of integrated pathways and control interventions - Ahman, Q.O.; Ugwu, C.S.; Didigwu, C.O.; John, S.O.; Adaji , I. (International Journal of Mathematical Analysis and Modelling, 2026)
Dengue fever remains a significant global health challenge, driven by complex interactions between human and mosquito populations. This study develops and analyzes a compartmental mathematical model to investigate the transmission dynamics of dengue virus, incorporating human and mosquito populations. The model captures key disease progression stages, including susceptible, exposed, infectious, and recovered compartments for humans, and susceptible, exposed, and infectious compartments for mosquitoes. Numerical simulations reveal critical trends in the human and mosquito populations, highlighting peak infection periods and the interplay between host and vector dynamics. Sensitivity analysis using Partial Rank Correlation Coefficients (PRCC) identifies key parameters influencing the basic reproduction number, such as transmission probabilities, mosquito biting rates, and progression rates. The results emphasize the importance of integrated vector management, personal protective measures, and healthcare interventions to mitigate dengue outbreaks. These findings provide actionable insights for designing targeted public health strategies and inform future research to improve dengue control and prevention.